How the brain connects in response to acute stress: A review at the human brain systems level. (December 2017) - van Oort, J.; Tendolkar, I.; Hermans, E.J.; Mulders, P.C.; Beckmann, C.F.; Schene, A.H.; Fernández, G.; van Eijndhoven, P.F.
Highlights: In health acute stress induces large scale changes at the brain's network level. The stress response can be described by the dynamical interactions of three networks. The salience and default mode network are both activated by acute stress. Stress may as well improve as deteriorate central executive network functioning. Changes in these three networks account for neuropsychological changes under stress. Abstract: The brain's response to stress is a matter of extensive neurocognitive research in an attempt to unravel the mechanistic underpinnings of neural adaptation. In line with the broadly defined concept of acute stress, a wide variety of induction procedures are used to mimic stress experimentally. We set out to review commonalities and diversities of the stress-related functional activity and connectivity changes of functional brain networks in healthy adults across procedures. The acute stress response is consistently associated with both increased activity and connectivity in the salience network (SN) and surprisingly also with increased activity in the default mode network (DMN), while most studies show no changes in the central executive network. These results confirm earlier findings of an essential, coordinating role of the SN in the acute stress response and indicate a dynamic role of the DMN whose function is less clear. Moreover, paradigm specific brain responses have to be taken into account when investigating the role and the within and between network connectivity of these three networks.